Wireless monitoring of power consumption for industrial robot during a pick and place task for predictive maintenance - Fadhil J.A.; Hussein A.F.; Qudr L.A.Z.; Sabry A.H. (Little Lion Scientific, 2023)
Industrial companies follow different maintenance strategies to increase operational reliability and reduce costs. One way to reduce maintenance costs is by real-time inspection of power consumptions to predict the potential failure of industrial machines. Wireless monitoring is essential as it provides safe and remote measuring for such applications. Related studies utilized efficient devices and strategies for monitoring the energy consumption of industrial machines, but didn't present a cost-effective and simple design accurately monitoring the power for multi-degree of freedom (MDOF) robots. The objective of this work is to develop a cost-effective wireless power consumption monitoring system enhancing predictive maintenance purposes for MDOF industrial robots. Unlike the traditional Zigbee-based WSN mentioned in the literature, the presented scheme includes only two RF modules, a single remote-sensing node called router XBee and another module at the monitoring station connected to a PC. The key feature of this cost-effective design is the ability to measure, process, and transfer data required to perform energy monitoring by only using two modules. ABB-IRB-1200 robot manipulator is used as a practical platform to test the effectiveness of the developed design. The measurement of power consumption is conducted via performing a task called pick- and-place by the robot. The produced consumption profile of the robot input power can be used further for energy modeling and estimation. 2021 Little Lion Scientific. All rights reserved.